A network analysis of gene co-expression in post-mortem brain tissues identifying novel genes and biological pathways underlying major depression - Yan, Miaomiao; Chen, Man; Jiang, Qin; Huang, Huilan; Wu, Yigao (Frontiers in Psychiatry, 2025)
IntroductionMajor Depressive Disorder (MDD), also known simply as depression, is a serious and common mood disorder. However, the potential pathogenesis and target genes of the disease have not been well illustrated.MethodsWe identified differentially expressed genes(DEG) using the published transcriptome data GSE80655 from postmortem brain tissues of 69 MDD patients, 71 Bipolar Disorder (BD) patients, and 71 Schizophrenia(SZ) patients and 70 controls. Another brain expression dataset included geneexpression profiles from six cortical and limbic brain regions of 34 patients with MDD and 55 control subjects without any history of psychiatric or neurological disorders. GO enrichment analysis was performed on DEGs.Weighted gene Co-expression network analysis (WGCNA) was conducted on DEGs. Subsequently,we extracted the modules determined by WGCNA and calculated the correlation of the modules with diseases or brain tissue regions. The modules specifically related to MDD were screened. Module genes are employed for gene function enrichment analysis.Enriched genes in biological pathways are used to construct the gene regulatory network, and the genes with the highest connectivity are classified as hub genes.ResultsDEGs related to MDD, BD, or SZ were screened. And by WGCNA, we determined the gene modules associated with MDD but not with BD and SZ. The MDD-related modules were further compared with the gene expression data from postmortem brain tissue of MDD patients in another group, and one of the gene modules which was enriched in the biological pathway related to mitochondrial oxidative phosphorylation and ubiquitination, was screened.Gene regulatory network analysis showed that the hub genes were PARK2, CUL1, SKP1, CYC1, and ATP5A1.The mitochondrial oxidative phosphorylation and ubiquitination related biological pathways are involved in the process of MDD.DiscussionThe hub genes may provide possible candidates for MDD targeted therapy that is worth exploring.